Prognostic Value of HER2 to CEP17 Ratio on Fluorescence In Situ Hybridization Ratio in Patients with Nonmetastatic HER2‐Positive Inflammatory and Noninflammatory Breast Cancer Treated with Neoadjuvant Chemotherapy with or without Trastuzumab. (31st January 2020) - Kogawa, Takahiro; Fujii, Takeo; Wu, Jimin; Harano, Kenichi; Fouad, Tamer M.; Liu, Diane D.; Shen, Yu; Masuda, Hiroko; Krishnamurthy, Savitri; Chavez‐MacGregor, Mariana; Lim, Bora; Murthy, Rashmi K.; et al.
Abstract: Background: We previously reported that in patients with HER2‐positive (HER2+) locally advanced breast cancer treated with neoadjuvant trastuzumab‐containing regimens, high HER2 to centromere enumerator probe 17 ratio on fluorescence in situ hybridization (HER2 FISH ratio) was an independent predictor of high pathologic complete response (pCR) rate, which translated into improved recurrence‐free survival (RFS). We sought to determine whether high HER2 FISH ratio is a predictor of pCR and prognosis in patients with HER2+ nonmetastatic inflammatory breast cancer (IBC) and non‐IBC treated with neoadjuvant chemotherapy with or without trastuzumab. Materials and Methods: This study included all patients with histologically proven stage III, HER2+ primary IBC, and non‐IBC treated with neoadjuvant chemotherapy with or without trastuzumab and definitive surgery during 1999–2012. Univariate and multivariate logistic regression models were applied to assess the effect of covariates on pCR. Kaplan‐Meier estimates with log‐rank test were employed for survival analysis. Univariate and multivariate Cox proportional hazards models were used to assess the effect of covariates on RFS and overall survival (OS). Results: The study included 555 patients with stage III, HER+ breast cancer, 181 patients with IBC, and 374 with non‐IBC. In the IBC cohort, HER2 FISH ratio was not significantly associated with pCR, RFS, or OS. In the non‐IBC cohort, higher HER2 FISH ratio was significantly associated with higher pCR rate and longer OS. Conclusion: HER2 FISH ratio showed prognostic value among patients with HER2+ non‐IBC but not HER2+ IBC treated with neoadjuvant chemotherapy. This disparity may be due to the underlying aggressive nature of IBC. Implications for Practice: The findings of this study indicate that the HER2 to fluorescence in situ hybridization ratio as a continuous variable has promise as a predictor of pathologic complete response to neoadjuvant chemotherapy in patients with HER2‐positive (HER2+) noninflammatory breast cancer (non‐IBC) regardless of the results on HER2 immunohistochemical testing. In the future, some patients with HER2+ non‐IBC and a high HER2 FISH ratio might even be offered personalized treatment options, such as nonsurgical treatment. Abstract : This article reports results of a study aimed to determine whether high HER2/CEP17 ratio on fluorescence in situ hybridization is a predictor of pathologic complete response rate and prognosis in patients with HER2+ non‐metastatic inflammatory breast cancer (IBC) and non‐IBC treated with neoadjuvant chemotherapy with or without trastuzumab.